2019
DOI: 10.1186/s40644-019-0251-3
|View full text |Cite
|
Sign up to set email alerts
|

Are baseline ultrasound and mammographic features associated with rates of pathological completes response in patients receiving neoadjuvant chemotherapy for breast cancer?

Abstract: Background Increasing numbers of breast cancer patients receive neoadjuvant chemotherapy (NACT). We seek to investigate whether baseline mammographic and ultrasound features are associated with complete pathological response (pCR) after NACT. Methods A database of NACT patients was reviewed. Baseline imaging parameters assessed were ultrasound: posterior effect; echo pattern; margin and lesion diameter; mammography: spiculation and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 28 publications
3
25
1
Order By: Relevance
“…More complex assessments using shear-wave US for TNBC have failed to demonstrate a benefit beyond the use of grayscale US employed here. [33][34][35] Although breast MRI has been proposed to be the imaging modality of choice for the early evaluation of early treatment responses to NAST, the use of MRI for this purpose in clinical practice has been limited because of the lack of consistency and standardization of specific MRI parameters that hold greater potential for early prediction of a pCR to NAST and the cost and the complexity of breast MRI. [36][37][38] In contrast, conventional breast US is widely accessible, and this can facilitate the implementation of serial US examinations to monitor treatment response.…”
Section: Discussionmentioning
confidence: 99%
“…More complex assessments using shear-wave US for TNBC have failed to demonstrate a benefit beyond the use of grayscale US employed here. [33][34][35] Although breast MRI has been proposed to be the imaging modality of choice for the early evaluation of early treatment responses to NAST, the use of MRI for this purpose in clinical practice has been limited because of the lack of consistency and standardization of specific MRI parameters that hold greater potential for early prediction of a pCR to NAST and the cost and the complexity of breast MRI. [36][37][38] In contrast, conventional breast US is widely accessible, and this can facilitate the implementation of serial US examinations to monitor treatment response.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies evaluated the reliability of imaging approaches, including ultrasound, mammography, and MRI, in predicting breast pCR after NST. However, the accuracy of these techniques was far from satisfactory (12)(13)(14)(15)(16)(17). Some early studies reported that using radiotherapy alone (without breast surgery) as the local treatment approach for breast cancer patients with cCR on imaging will lead to much higher rates of relapses (31)(32)(33).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies focus on the accuracy and reliability of non-invasive imaging methods to predict breast pCR, but the results are far from satisfactory. Neither ultrasound nor mammography is reliable with false negative rates (FNR) ranging from 9 to 70% ( 12 14 ). Similarly, magnetic resonance imaging (MRI) demonstrated an FNR up to 30–50% in predicting breast residual tumor after NST ( 15 17 ).…”
Section: Introductionmentioning
confidence: 99%
“…Mammography together with breast ultrasound (US) has been used to measure residual tumor burden during neoadjuvant therapy. While the resolution of some baseline mammographic features such as microcalcifications and spiculation of masses are associated with response [38], the use of mammography may be of limited value during neoadjuvant therapy due to variable accuracy and sensitivity to changes in residual tumor burden [39].…”
Section: Mammographymentioning
confidence: 99%
“…In a study of 159 patients, the percent change in US-measured tumor size at mid-treatment was linearly associated with the RCB index score in triple-negative (TN) and hormonal positive (HR+; ER or progesterone (PR) receptor positive or both) subtypes, but not in HER2+ tumors [ 59 ]. US imaging features such as the absence of posterior acoustic shadowing and spiculation were significant predictors of pCR in HER2+ tumors [ 38 ]. On the other hand, no feature was found to associate with response in the TN subtype, and the presence of posterior shadowing was associated with HR+/HER2− breast cancers [ 60 ].…”
Section: Imaging Of Neoadjuvant Treatment Response In Breast Cancementioning
confidence: 99%